2018
DOI: 10.1016/j.bbrc.2018.08.195
|View full text |Cite
|
Sign up to set email alerts
|

Daunorubicin, a topoisomerase II poison, suppresses viral production of hepatitis B virus by inducing cGAS-dependent innate immune response

Abstract: Hepatitis B virus (HBV) causes hepatic diseases such as chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma. These diseases are closely associated with persistent HBV infection. To prevent the progression of hepatic diseases, it is thus important to suppress persistent HBV infection. Daunorubicin (DNR), a topoisomerase II (Top II) poison, is a clinically used anticancer agent with a wide spectrum of activity against malignancies. DNR was recently reported to cause DNA damage-dependent interferon (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…Overall, the report suggests that doxorubicin-mediated IFN activation may be due to two distinct, ATM- or STING-dependent pathways. Another recent paper on hepatitis B virus (HBV) showed that daunorubicin can trigger innate immune response in a cGAS-dependent manner preventing HBV production in human hepatocytes [ 131 ]. Therefore, overall these results support the fact that anthracyclines can activate the STING-cGAS pathway activating type I interferons in cancer cells.…”
Section: Interactions Of Anthracyclines With the Immune Systemmentioning
confidence: 99%
“…Overall, the report suggests that doxorubicin-mediated IFN activation may be due to two distinct, ATM- or STING-dependent pathways. Another recent paper on hepatitis B virus (HBV) showed that daunorubicin can trigger innate immune response in a cGAS-dependent manner preventing HBV production in human hepatocytes [ 131 ]. Therefore, overall these results support the fact that anthracyclines can activate the STING-cGAS pathway activating type I interferons in cancer cells.…”
Section: Interactions Of Anthracyclines With the Immune Systemmentioning
confidence: 99%
“…Thus, further investigation of their roles in HBV infection is warranted. Although activation of the cGAS-STING pathway was demonstrated to be able to inhibit HBV replication in cell culture and mice (7,15,18,40), HBV could also actively suppress cGAS expression and function in vitro and humanized liver chimeric mice (40). Our results showed cGAS expression level was not altered in chronic HBV patients, suggesting HBV may evade from cGAS sensing.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, further investigation of their roles in HBV infection is warranted. Although activation of the cGAS-STING pathway was demonstrated to be able to inhibit HBV replication in cell culture and mice[18][19][45][46], HBV could also actively suppress cGAS expression and function in vitro and humanized liver chimeric mice[46]. Our results showed cGAS expression level was not altered in chronic HBV patients, suggesting HBV may evade from cGAS sensing.…”
mentioning
confidence: 63%